Punkuri mural art, nepeña, ancash - Samaniego Román, Lorenzo A. (2012)
Buildings constructed with hand-molded bricks of various shapes and then diligently coatings, such Punkuri (Nepeña) and Sechin (Casma) served for the use of color, running low and high relief, such as sculpture in the non-exempt being represented deities, mythical scenes-religious, with the intervention of man, fauna, flora and natural phenomena. The mural art of these buildings was linked to the religious, the worldview of the Andean people and is part of the visual language of the artists of the era, such as Punkuri that contributed to the development of artistic style Sechin, present in most of Archaic and Formative periods, probably between 4 000 to 1 000 years before Christ.